Spectrum Sharing in an ISM Band: Outage Performance of a Hybrid DS/FH Spread Spectrum System with Beamforming. (9th November 2009) - Li, Hanyu; Syed, Mubashir; Yao, Yu-Dong; Kamakaris, Theodoros
Abstract : This paper investigates spectrum sharing issues in the unlicensed industrial, scientific, and medical (ISM) bands. It presents a radio frequency measurement setup and measurement results in 2.4 GHz. It then develops an analytical model to characterize the coexistence interference in the ISM bands, based on radio frequency measurement results in the 2.4 GHz. Outage performance using the interference model is examined for a hybrid direct-sequence frequency-hopping spread spectrum system. The utilization of beamforming techniques in the system is also investigated, and a simplified beamforming model is proposed to analyze the system performance using beamforming. Numerical results show that beamforming significantly improves the system outage performance. The work presented in this paper provides a quantitative evaluation of signal outages in a spectrum sharing environment. It can be used as a tool in the development process for future dynamic spectrum access models as well as engineering designs for applications in unlicensed bands.